A new method to recover L-tyrosine from E. coli fermentation broth. Issue 1 (1st January 2020) - Li, Guohua; Liu, Jingyang; Chen, Ning; Xu, Qingyang
ABSTRACT: Although the production of L-tyrosine by recombinant Escherichia coli has been widely reported, L-tyrosine recovery from the fermentation broth has been rarely reported. Methods to recover L-tyrosine from the broth after alkaline lysis of the bacterial cells have been described. However, the broth becomes viscous and dark following cell lysis, making further extraction and purification difficult. Here, a new method for L-tyrosine extraction and purification from the fermentation broth without the lysis of bacteria is reported. First, acids, rather than bases, were used to dissolve L-tyrosine in the broth without causing lysis of the bacterial cells. E. coli cells in the broth were then removed through centrifugation. Activated carbon was then used to decolorize the supernatant containing L-tyrosine. Finally, sodium hydroxide was added to the clarified L-tyrosine solution for isoelectrocrystallization. L-tyrosine was obtained after filtration and drying. The recovery yield of L-tyrosine was 92%, and the purity was >98.5%, indicating high efficiency of the new method of L-tyrosine recovery from fermented broth. Furthermore, the method provides a reference for the extraction of guanosine, inosine, hypoxanthine, and other biological fermentation products.